Sêrat Bayanullah: A study of Raden Panji Natarata"s thoughts on Javanese Sufism through classical Javanese literature - Rahmawati, Mila I. (HTS teologiese studies, 2022)
This study describes Raden Panji Natarata’s thoughts as a humanist, poet and religious scholar who thinks that the concepts of Javanese Sufism and Islamic Sufism are two contradictory ideas. Raden Panji Natarata describes his ideas through the medium of têmbang macapat (Javanese song) in a classic Javanese literature entitled Sêrat Bayanullah. Sêrat Bayanullah, which is used as a source of data for this research, is a collection of the Pura Mangkunegaran library, Surakarta, with catalogue number A-393. The scope of this study focuses on Raden Panji Natarata’s thoughts on the nature of life, which include the concepts of human creation, human death, and the after-death union of the servant with God. To obtain objective and comprehensive research results, the researchers used a qualitative descriptive research paradigm by applying hermeneutic theory. The results showed that Raden Panji Natarata’s thoughts about the nature of life did not go beyond the limits of monotheism, while other poets tended to acculturate Javanese Sufism thoughts, which sometimes were not in line with the teachings of monotheism.Contribution: As an academic contribution, this research is expected to enrich and preserve the repertoire of local research literature with Sufism nuances and their relationship with the thoughts of Sufi experts. Differences in perspective is natural, and the most important thing is mutual respect for differing opinions for the sake of creating harmony in life.